3, 3-Diazidoenones – new types of highly reactive bis-azides. Preparation and synthetic transformations. Issue 3 (19th December 2018) - Lemport, Pavel S.; Smolyar, Ivan V.; Khrustalev, Victor N.; Roznyatovsky, Vitaly A.; Popov, Alexander V.; Kobelevskaya, Valentina A.; Rozentsveig, Igor B.; Nenajdenko, Valentine G.
Abstract : A new family of highly reactive 3, 3-diazidoenones was obtained. Their chemistry was investigated by both experimental studies and DFT calculations. Abstract : The interaction of geminal dichlorovinylketones with sodium azide was investigated by NMR and DFT calculations. It was found that the corresponding geminal 3, 3-diazidoenones are the resultant species. These highly reactive compounds can be trapped with cyclooctyne to form bis-triazolyl substituted enones. In the absence of a trapping agent, 3, 3-diazidoenones do cyclize into 3-azidoisoxazoles with the elimination of molecular nitrogen. The versatile reactivity of the resultant azidoisoxazoles was demonstrated in reactions with phosphorus(iii ) derivatives, Huisgen 1, 3-dipolar cycloaddition and Dimroth cyclization to provide efficient access to a variety of valuable compounds.